2020
DOI: 10.3389/fphar.2020.01044
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Microenvironment in MDS: The Final Frontier

Abstract: Myelodysplastic syndromes (MDS) are a heterogeneous group of malignant disorders of hematopoietic stem and progenitor cells (HSPC), mainly characterized by ineffective hematopoiesis leading to peripheral cytopenias and progressive bone marrow failure. While clonal dominance is nearly universal at diagnosis, most genetic mutations identified in patients with MDS do not provide a conspicuous advantage to the malignant cells. In this context, malignant cells alter their adjacent bone marrow microenvironment (BME)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 96 publications
(120 reference statements)
1
11
0
Order By: Relevance
“…Both treatment-na€ ıve and treated CLL patients were at increased risk of MDS and, theoretically, these observations could be driven by effects of CLL on the bone marrow microenvironment. 15 As more treatment options become available for patients with CLL, further characterization of their individual sets of late effects becomes increasingly important for informed choice of therapy. For MDS, our analyses suggested that the risk was particularly increased for patients receiving fludarabine containing regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Both treatment-na€ ıve and treated CLL patients were at increased risk of MDS and, theoretically, these observations could be driven by effects of CLL on the bone marrow microenvironment. 15 As more treatment options become available for patients with CLL, further characterization of their individual sets of late effects becomes increasingly important for informed choice of therapy. For MDS, our analyses suggested that the risk was particularly increased for patients receiving fludarabine containing regimens.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been hypothesized that the interaction of MDS blasts and the BM microenvironment might play an important role for disease homeostasis. More precisely, a bidirectional crosstalk between MDS clone and BM microenvironment seems to maintain the malignant clone, but also shape the BM environment [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to TAMs, the influence of niche stem cells on tumor development and drug resistant is also relevant. Interestingly, many studies have shown that STAT activity is essential to localize, maintain, and renew Hematopoietic Stem/Progenitors cells (HSPC) into tumoral niche and that STAT hyperactivation is associated with uncontrolled proliferation of HSPC (151)(152)(153)(154)(155). Thereby, dual strategies targeting both tumor cell proliferation and tumor niche and/or regulation of TIM represent a promising therapeutic strategy (156,157).…”
Section: Signal Transducers and Activators Of Transcription (Stat)mentioning
confidence: 99%